NFκB‐inducing kinase inhibits NFκB activity specifically in neurons of the CNS. Issue 2 (15th March 2016) - Mao, Xianrong; Phanavanh, Bounleut; Hamdan, Hamdan; Moerman‐Herzog, Andréa M.; Barger, Steven W.
Abstract: The control of NFκB in CNS neurons appears to differ from that in other cell types. Studies have reported induction of NFκB in neuronal cultures and immunostaining in vivo, but others have consistently detected little or no transcriptional activation by NFκB in brain neurons. To test if neurons lack some component of the signal transduction system for NFκB activation, we transfected cortical neurons with several members of this signaling system along with a luciferase‐based NFκB‐reporter plasmid; RelA was cotransfected in some conditions. No component of the NFκB pathway was permissive for endogenous NFκB activity, and none stimulated the activity of exogenous RelA. Surprisingly, however, the latter was inhibited by cotransfection of NFκB‐inducing kinase (NIK). Fluorescence imaging of RelA indicated that co‐expression of NIK sequestered RelA in the cytoplasm, similar to the effect of IκBα. NIK‐knockout mice showed elevated expression of an NFκB‐reporter construct in neurons in vivo . Cortical neurons cultured from NIK‐knockout mice showed elevated expression of an NFκB‐reporter transgene. Consistent with data from other cell types, a C‐terminal fragment of NIK suppressed RelA activity in astrocytes as well as neurons. Therefore, the inhibitory ability of the NIK C‐terminus was unbiased with regard to cell type. However, inhibition of NFκB by full‐length NIK is a novel outcome that appears to be specific to CNS neurons. This has implications for unique aspects of transcription in the CNS, perhaps relevant to aspects of development, neuroplasticity, and neuroinflammation. Full‐length NIK was found to inhibit (down arrow) transcriptional activation of NFκB in neurons, while it elevated (up arrow) activity in astrocytes. Deletion constructs corresponding to the N‐terminus or C‐terminus also inhibited NFκB in neurons, while only the C‐terminus did so in astrocytes. One possible explanation is that the inhibition in neurons occurs via two different mechanisms, including the potential for a neuron‐specific protein (e.g., one of the 14‐3‐3 class) to create a novel complex in neurons, whereas the C‐terminus may interact directly with NFκB. [Structure of NIK is based on Liu J., Sudom A., Min X., Cao Z., Gao X., Ayres M., Lee F., Cao P., Johnstone S., Plotnikova O., Walker N., Chen G., and Wang Z. (2012) Structure of the nuclear factor κB‐inducing kinase (NIK) kinase domain reveals a constitutively active conformation. J Biol Chem. 287, 27326‐27334); N‐terminal lobe is oriented at top]. Abstract : Full‐length NIK was found to inhibit (down arrow) transcriptional activation of NFκB in neurons, while it elevated (up arrow) activity in astrocytes. Deletion constructs corresponding to the N‐terminus or C‐terminus also inhibited NFκB in neurons, while only the C‐terminus did so in astrocytes. One possible explanation is that the inhibition in neurons occurs via two different mechanisms, including the potential for a neuron‐specific protein (e.g., one of the 14‐3‐3 class) to create a novel complex in neurons, whereas the C‐terminus may interact directly with NFκB. [Structure of NIK is based on Liu J., Sudom A., Min X., Cao Z., Gao X., Ayres M., Lee F., Cao P., Johnstone S., Plotnikova O., Walker N., Chen G., and Wang Z. (2012) Structure of the nuclear factor κB‐inducing kinase (NIK) kinase domain reveals a constitutively active conformation. J Biol Chem. 287, 27326‐27334); N‐terminal lobe is oriented at top].